Secondary forests in swidden agriculture inthe highlands of Thailand - Schmidt-Vogt, D. (2001)
Swidden farming is the main agent of conversion of primary forests to secondary forests in the highlands of mainland Southeast Asia, but there is a deterioration and decline of the practice with land use intensification. The population growth in northern Thailand has forced lowland farmers practising permanent wet rice cultivation to turn to short rotation swidden in the foot hill zone. Highland swidden agriculturists are adopting more intensive forms of swidden or are shifting to permanent farming. This change is supported by road construction and increased marketing opportunities for temperate crops grown in the highlands. The decline of swidden farming is causing a net degradation and decrease in fallow related secondary forest cover, with consequent losses in the biodiversity and economic potential of these forests. There exists no policy or legal framework in Thailand that allows for the preservation and sustainable legal use of these forests. Major obstacles for the development of such a framework are the prevailing assessment of secondary vegetation as degraded scrub, and a highland development policy that does not encourage forest use by local communities. The introduction of community forestry legislation is still pending. There is a need to design land use systems that integrate fallow forest management with agricultural production.